2019
DOI: 10.1186/s13613-019-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical septic shock research: why we need an animal ICU

Abstract: Animal experiments are widely used in preclinical medical research with the goal of disease modeling and exploration of novel therapeutic approaches. In the context of sepsis and septic shock, the translation into clinical practice has been disappointing. Classical animal models of septic shock usually involve one-sex-one-age animal models, mostly in mice or rats, contrasting with the heterogeneous population of septic shock patients. Many other factors limit the reliability of preclinical models and may contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 109 publications
(99 reference statements)
0
44
0
Order By: Relevance
“…They undertook a meta-analysis reviewing both experimental models and clinical studies and reported variable results on mitochondrial function depending on the species, organ, and time point investigated ( 90 ). However, the available experimental literature mainly originates from young and otherwise healthy animals, which does not represent the more frequent clinical scenario of elderly patients with comorbidities, a common pitfall of experimental studies in shock research in general ( 43 ). Nevertheless, there is elegant clinical evidence that despite adequate resuscitation, reduced mitochondrial respiration is (i) present in patients after the initial management of circulatory shock, and (ii) associated with worse outcomes.…”
Section: Evidence For Cellular Energetic Failure Resulting From Reducmentioning
confidence: 99%
See 1 more Smart Citation
“…They undertook a meta-analysis reviewing both experimental models and clinical studies and reported variable results on mitochondrial function depending on the species, organ, and time point investigated ( 90 ). However, the available experimental literature mainly originates from young and otherwise healthy animals, which does not represent the more frequent clinical scenario of elderly patients with comorbidities, a common pitfall of experimental studies in shock research in general ( 43 ). Nevertheless, there is elegant clinical evidence that despite adequate resuscitation, reduced mitochondrial respiration is (i) present in patients after the initial management of circulatory shock, and (ii) associated with worse outcomes.…”
Section: Evidence For Cellular Energetic Failure Resulting From Reducmentioning
confidence: 99%
“…Based on this rationale, fluid resuscitation ( 30 34 ), dobutamine ( 35 ), levosimendan ( 36 ), milrinone ( 37 ), nitric oxide (NO) donors ( 38 40 ), and prostacyclin (PGI 2 ) ( 40 42 ) have all been tested. In experimental settings, this approach was often successful but the majority of animal studies were only of short duration and/or did not include standard intensive care measures, which may limit transferability into clinical practice ( 43 ). Given the potential NO- or NO-derivatives induced uncoupling of mitochondrial respiration and inhibition of complex I and complex IV ( 14 , 44 46 ), caution must be taken with NO-donors as a therapeutic strategy to avoid detrimental effects on the mitochondria.…”
Section: Does “Microvascular Resuscitation” Help?mentioning
confidence: 99%
“…Current Protocols in Immunology sepsis models, including the use of antibiotics, fluid resuscitation, and monitoring of vital processes (Guillon et al, 2019).…”
Section: Of 16mentioning
confidence: 99%
“…Here, we suggest that the most translational sepsis model is used, e.g. an animal model with full intensive care unit (ICU) support [117].…”
Section: What Needs To Change? Part 3 -Developing More Predictive Prementioning
confidence: 99%